Aristófanes e as leis de Sólon - Leão, Delfim (2018)
In the new edition of Solon’s laws by Leão & Rhodes (2015), his lawcode is directly mentioned in the comedies of Aristophanes for four times (Av. 1353-57 = Fr. 55a; Av. 1660-64 = Fr. 50a; Nub. 1178-95 = Fr. 123a; and Daitaleis, fr. 233 Kassel & Austin, apud Gal. Linguarum Hippocratis Explicatio, prooemium (xix. 66 Kuhn) = Fr. 41a), and three indirectly, through references in the scholia (ad Av. 1354 = Fr. 85c; ad Av. 1541 = Fr. 79/b; ad Eq. 658 = Fr. 64b). Despite this relative scarcity, those occurrences prove that Aristophanes was familiar with Solon’s laws, which he uses mainly for parodic purposes. The aim of this paper is to analyse those passages in their proper context and in comparison with passages from other authors, in order to discuss their validity as sources for the study of Solon’s laws.